Pengenalan Dan Pemanfaatan Tanaman Herbal Dalam Pengobatan Tradisional Anak Di Kelurahan Musam Pembangunan - Sari, nurmala; Sudewi, Sudewi; Hasanah, Fenny; Handayani, Salma; Gulo, Putra Penyabar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut Nyak Dhien, 2025)
The increasing public awareness of health has also influenced the utilization of herbal medicinal plants, which have long been used as an alternative treatment in Indonesia. This community service activity aims to provide knowledge to the residents of Musam Pembangunan Village regarding the use of herbal plants for children's health, as well as to enhance their awareness, motivation, and capacity in utilizing them. The activity was carried out on November 13, 2024, involving a team of lecturers and students using the Participatory Learning Action (PLA) method. This method includes counseling and observational assistance regarding various herbal medicinal plants found in the surrounding environment, such as galangal, coriander, bay leaves, ginger, turmeric, and temulawak. The activity was successfully conducted and received positive responses from the community. Residents of Musam Pembangunan Village gained better information and knowledge about the use of medicinal plants for children's health. They also became more aware of the importance of utilizing herbal plants for disease prevention and treatment in children. The utilization of herbal medicinal plants needs to be continuously enhanced through sustainable education. Participatory-based counseling, such as PLA, has proven effective in increasing community awareness and understanding of the benefits of herbal plants for children's health.